Assessing of Poverty Alleviation Model based on the Entrepreneurship Spirit in Tourism Villages - Aryaningsih, Ni Nyoman (International Journal of Psychosocial Rehabilitation, 2020)
The rapid development of the tourism industry raises various challenges and opportunities for economic activity. As a result, economic agglomeration appears in one region on one side, but there is economic disagreement in other regions that will cause new poverty, especially in rural areas. Village tourism development as a government policy is an alternative to alleviate rural poverty. The purpose of this study was to analyze the pattern of poverty alleviation in tourist villages based on the entrepreneurial spirit. Data were collected by survey, interview, and questionnaire. Data analysis techniques used inferential statistics with multi-variables. The results of the study show that the pattern of poverty alleviation in rural tourism can be done by building time discipline, creativity, access to information, mindset to create a value of opportunity, so as to form habits in life. The benefits of the results of this study can create employment opportunities for rural communities in order to prosper.